STAT6 variants and non-atopic asthma in Pakistani population - Riaz, Ayesha; Ahsan Riaz, Muhammad; Khan, Luqman; Shareef Masoud, Muhammad; Hussain, Ghulam; Iqbal, Muhammad; Qasim, Muhammad (Cellular and Molecular Biology, 2018)
Asthma a chronic airway inflammatory disease mainly characterized by airways obstruction. Airway hyper responsiveness particularly in eosinophils and inflammatory mediators affect the bronchial mucosa. Genetic association studies show the association of single nucleotide polymorphisms (SNPs) in the STAT6 gene with asthma risk. Role of Signal transducer and activator of transcription 6 (STAT6) is acute for T-helper 2 (Th2) mediated responses during allergic airway diseases. Objective was to investigate whether the two single nucleotide polymorphism (rs4559 and rs324011) in STAT6 gene are associated with non-atopic asthma risk in Pakistani population. One hundred (100) asthma patients with a positive family history with at least one-ï¬rst degree asthma affected relative were enrolled. Normal healthy individuals (n=100) were also included as control subjects in the current study. STAT6 SNPs rs4559 and rs324011 were genotyped using SNaPSHOT mini-sequencing assay and the obtained data was statistically analyzed by online SHEsis software. A case-control study for association of STAT6 polymorphisms rs4559 and rs324011 with asthma risk was performed. The SNP rs4559 was found statistically significantly associated with increased susceptibility of developing non-atopic asthma in Pakistani individuals. The SNP rs324011 polymorphism in intron 2 of STAT6 gene may be associated with increased susceptibility of the development of non-atopic asthma as a strong statistically significant difference in allele frequency and genotype was observed between asthmatics and controls showing association with non-atopic asthma in Pakistani individuals. rs4559 and rs324011SNPs in STAT6 found associated with non-atopic asthma risk. We observed the statistically significant association between STAT6 polymorphisms with intrinsic (non-atopic) asthma in Pakistani population.